2008
DOI: 10.1186/1471-2407-8-392
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of SLIT-ROBO transcripts in hepatocellular carcinoma reveals two groups of genes with coordinate expression

Abstract: Background: SLIT-ROBO families of proteins mediate axon pathfinding and their expression is not solely confined to nervous system. Aberrant expression of SLIT-ROBO genes was repeatedly shown in a wide variety of cancers, yet data about their collective behavior in hepatocellular carcinoma (HCC) is missing. Hence, we quantified SLIT-ROBO transcripts in HCC cell lines, and in normal and tumor tissues from liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…Additionally, Robo4 was down-regulated in hepatocellular carcinoma tissues compared to the normal liver tissue [33]. But Grone et al reported that Robo4 expression had no difference between colorectal cancer tissue and normal colorectal tissue [34].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Robo4 was down-regulated in hepatocellular carcinoma tissues compared to the normal liver tissue [33]. But Grone et al reported that Robo4 expression had no difference between colorectal cancer tissue and normal colorectal tissue [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a striking parallel to our findings, autocrine Slit-Robo over-expression degraded E-cadherin to promote epithelial-mesenchymal transition and tumor growth in human colorectal carcinoma lines (Zhou et al, 2011). Robo2 was also upregulated in various human hepatocellular carcinoma (HCC) lines (Avci et al, 2008), as was Ena (Hu et al, 2014); notably, HCC can invade the lumen of the bile duct (Carella et al, 1981). Moreover, upregulated Robo2 was linked to aggressive inflamma-tory breast cancer (Bieche et al, 2004), and Slit overexpression in pancreatic tumors triggered metastasis into lymphatic vessel lumens (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR SIP1 mRNA expression in colon cancer cell lines SW620, SW480 and hepatocellular carcinoma cell line SK-HEP-1 was determined by quantitative real-time PCR as described previously (Avci et al, 2008). The expression of SIP1 in cell lines was measured using ΔΔCt method and normalized to GAPDH gene.…”
Section: Western Blottingmentioning
confidence: 99%